SOIL TRANSMITTED HELMINTHS EGGS ON THE BODY OF FLIES - Muhammad Baharul Iman; Gita Dwi Prasasty; Susilawati Susilawati; Chairil Anwar; Dwi Handayani; Dalilah Dalilah (Majalah Kedokteran Sriwijaya, 2022)
Soil-Transmitted Helminths (STH) is defined as a parasitic intestinal worm that can infect humans through contaminated soil. STH is reported to have infected more than 1.5 billion people worldwide. STH infection can manifest in various gastrointestinal disorders such as diarrhea and malnutrition. Flies that are diptera insects can act as mechanical vectors of various parasites, including STH. Therefore, this study aimed to identify the types of flies and contamination of STH eggs on the outside of the fly’s body in traditional market. This type of research was a descriptive observational study with a cross-sectional design. The samples in this study were all flies caught using Aerial nets and WHO fly traps in Kamboja Market, Ilir Timur I district, Palembang. The place for processing and observing samples was carried out at the Medical Chemistry and Biooptics Laboratory of FK UNSRI. The results showed the number of flies obtained was 258, consisting of 4 species, 156 flies of Musca domestica 156 (60.5%), 97 flies of Chrysomya megacephala (37.6%), 3 flies of Fannia sp. (1.2%), and 2 flies of Lucilia sp. (0.7%). 258 flies were grouped into 36 samples was observed under the microscope to find STH egg contamination. Among the 36 samples examined, 9 samples (25%) were found consisting of 12 A. lumbricoides eggs, 1 T. trichiura egg, and 1 hookworm egg. It can be concluded that there was contamintaion of STH eggs on the outside of the fly’s body at traditional market.